Investigation into the Promotion and Instruction of Chinese Traditional Music in Liaocheng Peiwen School of Peking University - Guo Junyao; Chiu Dickson K.W. (SHS Web of Conferences, 2024)
This research investigates the promotion and instruction of Chinese Traditional music in Liaocheng Peiwen School of Peking University. The first author, an alum with a decade of pedagogical experience, examined the challenges faced by private schools in providing tailored regulatory frameworks for Chinese Traditional music education. We share practical experience, drawing on the successful establishment of the school-based course "Chinese Folk Music and Geography." As the course is offered each year during the geography exam for students in their second year of junior high school, singing folk songs while learning geography enables students to explore China's beautiful landscapes while broadening their horizons. Students can understand the connection between folk music and geography, assisting their preparation for the exam.